2018
DOI: 10.1371/journal.pone.0204511
|View full text |Cite
|
Sign up to set email alerts
|

Flexible foraging strategies in Pipistrellus pygmaeus in response to abundant but ephemeral prey

Abstract: There is growing recognition that with sympathetic management, plantation forests may contain more biodiversity than previously thought. However, the extent to which they may support bat populations is contentious. Many studies have demonstrated active avoidance of coniferous plantations and attributed this to the lack of available roost sites and low invertebrate density. In contrast, other work, carried out in plantation dominated landscapes have shown that certain bat species are able to exploit these areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…It is known that soft‐bodied Nemoteceran diptera are the main components of P. pygmaeus diet (Barlow et al, 1997 ). Coniferous forest habitats support high abundances of Nemoteceran diptera, e.g., midges, and P. pygmaeus will preferentially seek out the coniferous forest for foraging (Kirkpatrick et al, 2018 ). However, we mirror the sentiments of Salinas‐Ramos, Agnelli, Bosso, Ancillotto, Sánchez‐Cordero, et al ( 2021 ), who found changes in bat jaw morphology along a latitudinal gradient and hypothesized this may be due to a key variable relating to diet being absent from the data.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that soft‐bodied Nemoteceran diptera are the main components of P. pygmaeus diet (Barlow et al, 1997 ). Coniferous forest habitats support high abundances of Nemoteceran diptera, e.g., midges, and P. pygmaeus will preferentially seek out the coniferous forest for foraging (Kirkpatrick et al, 2018 ). However, we mirror the sentiments of Salinas‐Ramos, Agnelli, Bosso, Ancillotto, Sánchez‐Cordero, et al ( 2021 ), who found changes in bat jaw morphology along a latitudinal gradient and hypothesized this may be due to a key variable relating to diet being absent from the data.…”
Section: Discussionmentioning
confidence: 99%
“…It also forms nursery colonies much larger than those of P. pipistrellus [85], furtherly increasing its competitive potential. Moreover, due to flexible foraging strategies, P. pygmaeus is adapted to exploit abundant but ephemeral prey, such as small midges, forming large swarms around even-aged, intensively managed plantations of non-native conifers [86]. At least when foraging in riparian and wetland habitats, P. pygmaeus hunts mostly small dipterans belonging to the family Chironomidae, i.e., one of the most abundant groups of aquatic insects, which often increase in density through the anthropogenic eutrophication of waters [87].…”
Section: Factors Behind the Hyperabundance Of Pipistrellus Pygmaeus A...mentioning
confidence: 99%
“…B07 P. pygmaeus also uses trees as day roosts (Bartonička et al 2008, Kirkpatrick et al 2018, Dietz et al 2018 9 Conservation measures…”
Section: Long-term Trend Periodmentioning
confidence: 99%